A Ten-Minute Bioassay to Test Metal Toxicity with the Freshwater Flagellate Euglena agilis - Choi, Soyeon; Lee, Hojun; Lee, Min-Soo; Park, Joon Tae; Heynderickx, Philippe M.; Wu, Di; Depuydt, Stephen; Asselman, Jana; Janssen, Colin; Häder, Donat-Peter; Han, Taejun; Park, Jihae (Biology, 2022)
A chemical analysis of water quality cannot detect some toxicants due to time constraints, high costs, and limited interactions for detection. Bioassays would offer a complementary means to assess pollution levels in water. Euglena is a flagellate green alga and an excellent system for toxicity testing thanks to its ease of culture, rapid growth, and quick response to environmental stresses. Herein, we examined the sensitivity of E. agilis to seven heavy metals by analyzing six end-point parameters: motility, velocity, cell compactness, upward swimming, r-value, and alignment. Notably, the velocity of E. agilis was most sensitive to cadmium (96.28 mg·L−1), copper (6.51 mg·L−1), manganese (103.28 mg·L−1), lead (78.04 mg·L−1), and zinc (101.90 mg·L−1), while r-values were most sensitive to arsenic (12.84 mg·L−1) and mercury (4.26 mg·L−1). In this study, velocity and r-values are presented as useful biomarkers for the assessment of metal toxicity in Euglena. The metals As, Cd, Cu, and Pb were suitable for this test. The advantages of the ecotoxicity test are its rapidity: It takes 10 min to obtain results, as opposed to the typical 3–4 d of exposure time with intensive labor. Moreover, this test can be performed at room temperature under dark conditions.
CRIS-Team Scopus Importer:2022-11-25
Keywords: bioassays; end points; Euglena agilis; heavy metals